Evaluating the macroscopic system properties of kelp species planted on two artificial reefs: Implications for the restoration of perturbed subtidal areas. (5th May 2021) - Campos, Leonardo; Ortiz, Marco; Rodríguez-Zaragoza, Fabián
Abstract: Macroscopic ecosystem properties based on an Ascendency theoretical framework were assessed for mass-balance trophic models representing ecological systems constructed by the kelp species Macrocystis pyrifera planted on artificial reefs installed on subtidal barren rocky and sandy bottoms (Antofagasta Peninsula, Chile). Information on biomass, production, diet and consumption was needed. The magnitudes of relative Ascendency, relative Overhead and Redundancy values indicated that kelp planted on artificial reefs allocated on soft bottoms would be more highly developed and less resistant to perturbations than ecological systems on artificial reefs disposed on barren and natural systems inhabiting soft bottoms and kelp habitats. The relative Ascendency corresponding to each component of the ecological systems constructed on artificial reefs on both habitats was represented principally by detritus ( 37%), M. pyrifera (between 22 and 26%) and phytoplankton (between 10 and 13%). The compartments of Rhodophyta, Chlorophyta Mesophyllum sp. and the sea star Heliaster helianthus accounted for the system complexity in terms of flow, exhibiting the lowest Average Mutual Information. The Finn cycling index – considered as a ecosystem maturity index – showed contradictory outcomes compared to Ascendency. However, the values of System omnivory index and Average path length quantified for the ecological systems constructed on both artificial reefs showed similar network topologies compared to natural kelp beds. Based on our findings, artificial reefs seeded with M. pyrifera could be used to restore perturbed local marine benthic ecological systems along the Chilean coast. Likewise, this work shows that the trajectory of local ecological systems can be modified, enhancing their global-system health. Highlights: Trophic mass-balance models were built for two artificial reefs planted with kelp in northern Chile. The growth, development and maturity of kelp planted on artificial reefs were assessed and compared using Ascendency. Artificial reefs planted with kelp would be an effective tool to enhance the health of perturbed ecosystems.